2022
DOI: 10.21608/ejfs.2022.119141.1120
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, antioxidant, antimicrobial and sensory properties of functional yoghurt supplemented with guava seeds, leaves and pulp extract

Abstract: P SIDIUM GUAJAVA L., popularly known as guava has many medical benefits especially leaves and it considered as waste and seed was by product of juice industry. The aim of this study to investigate the effect of the phenolic and flavonoid compounds on antioxidant and antimicrobial activity of functional flavored yoghurt supplemented with guava extracts (GE) (seeds, green and red leaves and juice). The results showed that all guava extracts have antioxidant activity using (DPPH, ABTS) methods being (seed 89.18%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Furthermore, the GC-MS analysis showed several bioactive compounds with important biological activity in ABP like Cinnamic acid, 4-hydroxy-3-methoxy (which has a promising potential as anticancer according to Mumtaz et al 2021), 9,10-Secocholesta-5,7,10(19)triene-3,24,25-triol, (3α,5Z,7E)-(which has anti-eczematic, anti-osteoporotic and inhibits prostaglandin-E2 9-reductase (Brintha et al, 2017), 1-Monolinoleoylglycerol trimethyl silyl ether (antimicrobial activity according to Al Bratty et al (2020), Sarreroside (which has respiratory analeptic effect, anti-cancer, antiprotozoa, dementia treatment, hepatoprotectant, and anti-eczematic according to Brintha et al (2017), Oxiraneoctanoic acid, 3-octyl-, cis-(Actually, Hussein et al (2016a) showed that Oxiraneoctanoic acid, 3-octyl-,methyl ester had antibacterial activity), 7,8-Epoxylanostan-11ol, 3-acetoxy-(which has antimicrobial, antiinflammatory effect according to Hassan et al (2014); Lee et al (2013), and n-Butyl ricinoleate (it was mentioned to the anti-bacterial and antimycobacterial properties of ricinoleic acidderived compounds (Kuppala et al, 2016).…”
Section: Gas Chromatography and Mass Spectrometry Analysis (Gc-ms) An...mentioning
confidence: 99%
“…Furthermore, the GC-MS analysis showed several bioactive compounds with important biological activity in ABP like Cinnamic acid, 4-hydroxy-3-methoxy (which has a promising potential as anticancer according to Mumtaz et al 2021), 9,10-Secocholesta-5,7,10(19)triene-3,24,25-triol, (3α,5Z,7E)-(which has anti-eczematic, anti-osteoporotic and inhibits prostaglandin-E2 9-reductase (Brintha et al, 2017), 1-Monolinoleoylglycerol trimethyl silyl ether (antimicrobial activity according to Al Bratty et al (2020), Sarreroside (which has respiratory analeptic effect, anti-cancer, antiprotozoa, dementia treatment, hepatoprotectant, and anti-eczematic according to Brintha et al (2017), Oxiraneoctanoic acid, 3-octyl-, cis-(Actually, Hussein et al (2016a) showed that Oxiraneoctanoic acid, 3-octyl-,methyl ester had antibacterial activity), 7,8-Epoxylanostan-11ol, 3-acetoxy-(which has antimicrobial, antiinflammatory effect according to Hassan et al (2014); Lee et al (2013), and n-Butyl ricinoleate (it was mentioned to the anti-bacterial and antimycobacterial properties of ricinoleic acidderived compounds (Kuppala et al, 2016).…”
Section: Gas Chromatography and Mass Spectrometry Analysis (Gc-ms) An...mentioning
confidence: 99%